2000
DOI: 10.1177/0146167200263002
|View full text |Cite
|
Sign up to set email alerts
|

Motivated Stereotyping of Women: She’s Fine if She Praised Me but Incompetent if She Criticized Me

Abstract: Motivation may provoke stereotype use. In a field study of students' evaluations of university instructors and in a controlled experiment, participants viewed women as less competent than men after receiving negative evaluations from them but not after receiving positive evaluations. As a result, the evaluation of women depended more on the favorability of the feedback they provided than was the case for men. Most likely, this occurred because the motivation of criticized participants to salvage their self-vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
131
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 27 publications
9
131
0
2
Order By: Relevance
“…At a more fundamental level, research literature focused early on the validity and reliability of the instruments used to elicit students' reactions to teaching (Abrami 1989;Abrami et al 1990;Cohen 1981). Potential sources of bias in terms of response to teachers from the point of view of gender, age or perceived physical attractiveness have also been investigated (Ambady and Rosenthal 1993;Hamermesh and Parker 2003;Kaschak 1978;Sinclair and Kunda 2000). In the case of Zabaleta (2007), a range of potential ancillary variables that could impact on SET, such as class size, gender, age, experience of teachers, are examined.…”
Section: Introductionmentioning
confidence: 99%
“…At a more fundamental level, research literature focused early on the validity and reliability of the instruments used to elicit students' reactions to teaching (Abrami 1989;Abrami et al 1990;Cohen 1981). Potential sources of bias in terms of response to teachers from the point of view of gender, age or perceived physical attractiveness have also been investigated (Ambady and Rosenthal 1993;Hamermesh and Parker 2003;Kaschak 1978;Sinclair and Kunda 2000). In the case of Zabaleta (2007), a range of potential ancillary variables that could impact on SET, such as class size, gender, age, experience of teachers, are examined.…”
Section: Introductionmentioning
confidence: 99%
“…As Tatro (1995) found, one contextual factor that is highly salient to most students is grades, and there is reason to suspect that expected grade is related to students' evaluations in gendered ways. Sinclair and Kunda (2000) reported that students who received better grades also gave their college instructors higher evaluations, whereas low grades disproportionately reduced the ratings of women instructors in comparison to men instructors.…”
mentioning
confidence: 99%
“…It also is more important for female professors to be self-confident, stable, and steady (Burns-Glover & Veith, 1995). Women professors who give low grades or who do not have a warm expressive style are evaluated more negatively than their male counterparts (Sinclair & Kunda, 2000). Women faculty who lecture or who have a particularly informal style also may be evaluated more negatively than male colleagues demonstrating similar behaviors (Statham et al, 1991).…”
mentioning
confidence: 99%